A Falsification of the Citation Impediment in the Taxonomic Literature. (4th May 2015) - Steiner, Florian M.; Pautasso, Marco; Zettel, Herbert; Moder, Karl; Arthofer, Wolfgang; Schlick-Steiner, Birgit C.
Abstract : Current science evaluation still relies on citation performance, despite criticisms of purely bibliometric research assessments. Biological taxonomy suffers from a drain of knowledge and manpower, with poor citation performance commonly held as one reason for this impediment. But is there really such a citation impediment in taxonomy? We compared the citation numbers of 306 taxonomic and 2291 non-taxonomic research articles (2009–2012) on mosses, orchids, ciliates, ants, and snakes, using Web of Science (WoS) and correcting for journal visibility. For three of the five taxa, significant differences were absent in citation numbers between taxonomic and non-taxonomic papers. This was also true for all taxa combined, although taxonomic papers received more citations than non-taxonomic ones. Our results show that, contrary to common belief, taxonomic contributions do not generally reduce a journal's citation performance and might even increase it. The scope of many journals rarely featuring taxonomy would allow editors to encourage a larger number of taxonomic submissions. Moreover, between 1993 and 2012, taxonomic publications accumulated faster than those from all biological fields. However, less than half of the taxonomic studies were published in journals in WoS. Thus, editors of highly visible journals inviting taxonomic contributions could benefit from taxonomy's strong momentum. The taxonomic output could increase even more than at its current growth rate if: (i) taxonomists currently publishing on other topics returned to taxonomy and (ii) non-taxonomists identifying the need for taxonomic acts started publishing these, possibly in collaboration with taxonomists. Finally, considering the high number of taxonomic papers attracted by the journal Zootaxa, we expect that the taxonomic community would indeed use increased chances of publishing in WoS indexed journals. We conclude that taxonomy's standing in the present citation-focused scientific landscape could easily improve—if the community becomes aware that there is no citation impediment in taxonomy.